A simple and cost-effective method to measure moisture content for multigrain - Pruengam, Pimpan; Pathaveerat, Siwalak; Noypitak, Sirinad (International Journal of Agricultural Technology, 2025)
An integrated moisture inspection card was developed for measuring the moisture content of grains. The moisture content of paddy, corn, and soybean influenced the color change of cobalt chloride-coated paper. Experiments using corn and soybean with coated paper were conducted in a jar with head space of 25%, 50%, or 75%, with the lid closed for 30, 45, or 60 minutes. The results showed that the highest color value in corn and soybean was produced with a head space of 75% and a testing duration of 60 minutes (HS75DT60). This differed from paddy, where the highest color value was observed for HS75DT45. This discrepancy explained that corn and soybean are oil crops with a pericarp or seed coat. For all grains, using a testing duration of 45 minutes resulted to increase coefficient of correlation, indicating a better relationship between moisture content and color values. The card production process standardizes the printed RGB color values by converting from the L*, a*, and b* values. Additionally, the card was calibrated its relation to the moisture content of various grains, making it suitable for use in a wide variety of applications.